QUALITY OF LIFE OF CENTRAL NERVOUS SYSTEM TUMOR PATIENTSWITH CANCER PAIN - Karina; Henry Sugiharto; Yunni Diansari; Erial Bahar (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Cancer pain is the main symptom experienced by patients with central nervous system (CNS) tumors and significantly affects quality of life. A cross-sectional study at Dr. Mohammad Hoesin General Hospital, Palembang (March–June 2025) involved 89 patients using consecutive sampling. Data were obtained from medical records and structured interviews. Quality of life was assessed using the EORTC QLQ-30, while pain intensity was assessed using the NPRS. The majority of patients were female (56.2%), aged <60 years (75.3%), with secondary (55.1%) and intracranial (76.4%) tumors. Most experienced mild pain (56.2%) and received non-opioid therapy (70.8%). Results showed a moderate quality of life, with relatively high cognitive function, but pain intensity was negatively correlated with quality of life (r = -0.321; p = 0.002). Severe pain increased the risk of poor quality of life 4.7-fold, while tumor type increased the risk 5.1-fold. These findings confirm that effective pain management, appropriate analgesic selection, and definitive therapy play an important role in improving the quality of life of CNS tumor patients.